Pelatihan Penggunaan Canva Sebagai Media Pembelajaran Pendidikan di SMA 19 Gowa - Magfirah, Magfirah; Harlina, Sitti (Lembaga Penelitian Pengabdian kepada Masyarakat dan Publikasi Universitas Bhayangkara Jakarta Raya, 2025)
Good education is greatly influenced by the learning media used. The right media can make the teaching and learning process more effective and enjoyable, making it easier for students to understand the material. Apart from that, interesting media can also increase students' learning motivation. In Community Service (PKM) with the theme Training on Using Canva as a Learning Media at SMA 19 Gowa, this activity aims to provide learning to teachers so that they can use Canva as a teaching aid. The implementation method includes a direct approach, practice, preparing interesting material, providing facilities, guidance, and evaluation to measure the results of the questionnaires that we distribute. The results of the questionnaire showed that 15 female participants and 8 male participants felt very satisfied. The assessment of the PKM facilitator was also positive, with 13 female teachers and 6 male teachers assessing the facilitator as very good. In assessing the relevance of the training, 7 participants said it was very relevant, 1 participant was relevant, and 8 participants were quite relevant. The participants wanted ongoing material regarding the use of Canva in creating learning slides. Through this PKM, we have succeeded in providing a positive impact and new skills in using innovative learning media, so that teachers are expected to be more effective in teaching and improve the quality of education at SMA 19 Gowa.